Catch me a cowboy - Lane, Katie (New York : Forever, 2012)
After her husband's unexpected death, Shirlene Dalton, who had it all--a perfect marriage and an outrageous mansion--is determined to prove to the local gossips that she can make it on her own and finds an unexpected ally in her new neighbor, Billy Wilkes, who has his own score to settle